Starvation Time and Successive Collection Effects on Leeches Saliva Collection Quantity and Proteins Quality and Quantity in Wet Season - Mohamed Alaama,; Helaluddin, ABM.; Abbas Mohammad,; Ahmed Merzouk,; Abdualrahman M Abdualkader,; Mohamed Awang, (Universiti Kebangsaan Malaysia, 2014)
The salivary gland secretion of the haematophagous animals, leeches, has attracted the attention of therapists since the extreme old ages due to its wide range of medical properties. Thus, many researches have been done to develop and optimize new methods to collect leech saliva with high quality and quantity. In the present study, we aimed to evaluate the effects of starvation period and repeated collection on the quality and quantity of leech saliva extract LSE and its contents of proteins during the rainy season. Protein recovery in the LSE was also studied after first collection. It was found that leeches are able to produce protein-containing saliva whenever fed during the whole study period of 18 weeks with varied protein concentrations. The results showed that the highest protein concentrations (105-91 μg/mL) were produced after 12-15 weeks of starvation. The results of successive collection showed that leeches are able to produce proteins and peptides whenever they suck the solution after first collection with some varies in the concentrations. The concentrations varied between 0 and 72% of the initial concentration. Gel electrophoresis results showed absence for some bands when the concentrations are too low. Also the results showed that leeches are able to recover about 42% of their initial proteins concentration within four weeks of starvation after first feeding. The gel electrophoresis results showed the closeness between the first and second collections. To conclude, all test factors (starvation period, successive collection and recovery test) were shown to have an important impact on protein concentration of leech saliva and therefore its medicinal affectivity. The mentioned results are reported for the first time and they open the gate for further studies.